2020
DOI: 10.3390/nano10101902
|View full text |Cite
|
Sign up to set email alerts
|

Low Working Temperature of ZnO-MoS2 Nanocomposites for Delaying Aging with Good Acetylene Gas-Sensing Properties

Abstract: The long-term stability and the extension of the use time of gas sensors are one of the current concerns. Lowering the working temperature is one of the most effective methods to delay aging. In this paper, pure MoS2 and ZnO-MoS2 nanocomposites were successfully prepared by the hydrothermal method, and the morphological characteristics were featured by scanning electron microscopy (SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). Pure MoS2 and Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…For instance, various 2D materials and metal oxide-based gas sensors such as MoS 2 -reduced graphene oxide nanohybrid, MoS 2 @MoO 3 magnetic hetero-structure, wool-based carbon fiber/MoS 2 composite and ZnO-MoS 2 nanocomposites were used to detect various types of VOCs, accompanied by high response, good selectivity, rapid response/recovery times, etc. [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, various 2D materials and metal oxide-based gas sensors such as MoS 2 -reduced graphene oxide nanohybrid, MoS 2 @MoO 3 magnetic hetero-structure, wool-based carbon fiber/MoS 2 composite and ZnO-MoS 2 nanocomposites were used to detect various types of VOCs, accompanied by high response, good selectivity, rapid response/recovery times, etc. [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NH 3 exposure of more than 50 parts per million (ppm) can cause severe health-related issues as per United States health organization . Recently, layered metal dichalcogenides like MoS 2 , MoSe 2 , MoTe 2 , SnS 2 , WS 2 , and WSe 2 have emerged as new alternatives for NH 3 sensing owing to their extraordinary properties like high surface-to-volume ratio, catalytic property, ease of fabricating flexible wearable sensor, etc. However, the response of these layered material-based sensors is not adequate at room temperature and needs several strategies to improve the sensing performance, e.g., noble metal doping (such as Pt and Au), functionalization, composites with other materials, etc. Besides inventing new strategies to improve the sensing performance of the existing materials, it is also very much essential to introduce new functional materials for gas sensing, which may exhibit superior sensing performance. Bi 2 Se 3 is a metal chalcogenide (bandgap 0.3 eV) with a layered structure, where individual layers are stacked via a weak van der Waals interaction .…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments already demonstrated that multilayer MoS 2 -ZnO heteronanostructures could effectively increase the spectral absorption range and promote the separation and migration of carriers through the built-in electric fields, thereby improving the photoelectric response characteristics [14]. Several hybrid MoS 2 -ZnO nanomaterial-based prototypes such as flexible photodetectors and gas sensors have also been reported [26,27]. Based on this point, it is necessary to further study new heteronanostructures and heterojunctions in the MoS 2 /ZnO that may have new valuable applications in solar cells and self-powered photodetectors.…”
Section: Introductionmentioning
confidence: 99%